Variations in Phototroph Communities on the Ablating Bare-Ice Surface of Glaciers on Brøggerhalvøya, Svalbard - Takeuchi, Nozomu; Tanaka, Sota; Konno, Yudai; Irvine-Fynn, Tristram D. L.; Rassner, Sara M. E.; Edwards, Arwyn (Frontiers in Earth Science, 2019)
During the summer ablation season, Arctic glacier surfaces host a wealth of microbial life. Here, the phototroph communities on the ablating bare-ice surface of three valley glaciers on Brøggerhalvøya, Svalbard were investigated. The communities mainly comprised seven taxa of green algae and cyanobacteria, which have been commonly reported on Arctic glaciers. Although the geographical and glaciological settings of the three studied glaciers are similar, there were differences in total phototroph biomass. The community structure was also distinctive among the glaciers: high dominance of a single taxon of green algae (Ancylonema nordenskiöldii) for Midtre Lovénbreen, abundant cyanobacteria for Austre Brøggerbreen, and diverse green algae for Pedersenbreen. The major soluble ions in the surface ice showed that there was no significant difference in meltwater nutrient conditions between the glaciers, but there were lower concentrations of mineral-derived ions on Midtre Lovénbreen. Consequently, the glacier-specific mineral loading and surface hydrology are inferred to explain the contrast in bare ice algal communities between the glaciers. We hypothesize that local, glacier-specific conditions affect algal communities and the associated influences on carbon cycling and ice-surface albedo.